Feminist Conversations : Fuller, Emerson, and the Play of Reading - Zwarg, Christina, 1949- (Book collections on Project MUSE., 1995)
In a new account of the relationship between Margaret Fuller and Ralph Waldo Emerson, Christina Zwarg recreates a feminist conversation that has gone unheard. In Zwarg's view, the intimate, yet restrained, letters between the two writers are most significant in confronting the challenges posed by gender and desire. Focusing on their exploration of Charles Fourier's utopianism and particularly his concept of "passionate attraction," Zwarg offers the only detailed reading of Emerson's letters to Fuller.